2019
DOI: 10.1136/bmj.l4570
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response associations between accelerometry measured physical activity and sedentary time and all cause mortality: systematic review and harmonised meta-analysis

Abstract: ObjectiveTo examine the dose-response associations between accelerometer assessed total physical activity, different intensities of physical activity, and sedentary time and all cause mortality.DesignSystematic review and harmonised meta-analysis.Data sourcesPubMed, PsycINFO, Embase, Web of Science, Sport Discus from inception to 31 July 2018.Eligibility criteriaProspective cohort studies assessing physical activity and sedentary time by accelerometry and associations with all cause mortality and reported effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

81
1,035
12
34

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 1,106 publications
(1,162 citation statements)
references
References 46 publications
81
1,035
12
34
Order By: Relevance
“…The subgroup analyses and metaregression analyses both confirmed that more time spent in LPA was inversely associated with mortality risks, supporting previous systematic reviews and meta-analysis for general populations. 5,8,9,47 The present meta-analyses showed progressive decreases in mortality risk as people spend more time in LPA. Compared with the lowest LPA group, the risk of death decreased approximately 35% and 50% for participants spending between 5 and 7 h/d and more than 7 hours a day in LPA, respectively (Model 2 in Table 1).…”
Section: Discussionmentioning
confidence: 50%
“…The subgroup analyses and metaregression analyses both confirmed that more time spent in LPA was inversely associated with mortality risks, supporting previous systematic reviews and meta-analysis for general populations. 5,8,9,47 The present meta-analyses showed progressive decreases in mortality risk as people spend more time in LPA. Compared with the lowest LPA group, the risk of death decreased approximately 35% and 50% for participants spending between 5 and 7 h/d and more than 7 hours a day in LPA, respectively (Model 2 in Table 1).…”
Section: Discussionmentioning
confidence: 50%
“…A large body of literature has shown the effects of LTPA over general adult´s health worldwide in a dose‐response manner, reducing the risk of suffering a wide range of chronic diseases and all‐cause as well as case‐specific mortality . Further, even when adjusted for sedentary time, another critical risk factor for both chronic disease and mortality, physical activity showed to be a reliable predictor of all‐cause mortality . Thus, those LTPA protective properties might contribute to diminishing the risk of LTSA, since that has been highly associated with chronic conditions and early mortality Because aerobic capacity (ie, maximal oxygen consumption), as well as muscular strength, has been inversely associated with, respectively, cardiovascular disease morbidity and all‐cause mortality among adults, the LTSA risk might decrease when performing either endurance or strength training during leisure.…”
Section: Discussionmentioning
confidence: 99%
“…29 Further, even when adjusted for sedentary time, another critical risk factor for both chronic disease and mortality, 30 physical activity showed to be a reliable predictor of all-cause mortality. 31 Thus, those LTPA protective properties might contribute to diminishing the risk of LTSA, since that has been highly associated with chronic conditions 32 and early mortality 9 Because aerobic capacity (ie, maximal oxygen consumption), as well as muscular strength, has been inversely associated with, respectively, cardiovascular disease morbidity 33 and all-cause mortality among adults, 33,34 the LTSA risk might decrease when performing either endurance or strength training during leisure. Therefore, encouraging workers to move more as a general notion, regardless of the type of physical activity, might contribute to reducing LTSA levels in a general population of workers.…”
Section: Discussionmentioning
confidence: 99%
“…Although physical activity research has typically focused on MVPA, emerging evidence suggests that light intensity physical activity (LIPA) is associated with better cardiometabolic health, lower incidence of type 2 diabetes and all-cause mortality after adjusting for MVPA [2][3][4]. On the other hand, sedentary time is adversely associated with cardio-metabolic health [5,6], incidence of type 2 diabetes, cardiovascular disease [7] and all-cause mortality [8] independent of MVPA. Additionally, there is some evidence that both short and long sleep duration are adversely associated with body mass index (BMI), impaired glucose metabolism and blood pressure [9].…”
Section: Introductionmentioning
confidence: 99%